The Usage of Group Chatting Platform for English Skills - T I Prasojo; A M Mufid; M R Fadliansyah; T Tawami (Peneliti.net, 2021)
In this pandemic, many people will stay at their home rather than go outside, thus making it hard to live regular daily life for many people, including for people who are learning language. The purpose of this analysis is to find another way of learning English by using a group chat platform. The method that we will use is by joining a group chat server on one group chatting platform called “Discord”. The result of this analysis shows that joining a discord server you can talk with people from all around the world, study the use of grammar, test conversation skills, and measure English language understanding. From that result we can say that joining a discord server is another way of learning English without having to go outside and actually try your skill with a native speaker. In conclusion using discord is a good way to learn English in the pandemic era.